RANCANG BANGUN SISTEM INFORMASI P-COM EDUCATION CENTRE BERBASIS WEB - Rianis, Baiq; Bagye, Wire; Hamdi, Saeful (Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2023)
The Praya Computer Eduction Center is currently experiencing a decline in registration due to the lack of information that is widely disseminated to people who cannot be reached by previously used information media such as brochures, radio, newspapers and so on, therefore we need a medium that can be achieved by other alternatives. that can support the information spread widely, especially for those who are far away. In this study, the calculation of SUS data is used to determine the efficiency of this Education Information sistem. From the results of the blackbox test to sistem this information, it shows quite good results with no obstacles obtained when inputting, editing, deleting. For further follow-up, the management of the P-COM Education Center is expected to carry out more operations on this information sistem to obtain information SISTEM methods so that they can be used in the long term.